Gastrointestinal symptoms and nutritional issues in patients with hypermobility disorders: assessment, diagnosis and management. Issue 1 (8th June 2022) - Lam, Ching; Amarasinghe, Gehanjali; Zarate-Lopez, Natalia; Fikree, Asma; Byrne, Peter; Kiani-Alikhan, Sorena; Gabe, Simon; Paine, Peter
Abstract : Patients diagnosed with hypermobile Ehlers-Danlos syndrome and hypermobile spectrum disorders are increasingly presenting to secondary and tertiary care centres with gastrointestinal (GI) symptoms and nutritional issues. Due to the absence of specific guidance, these patients are investigated, diagnosed and managed heterogeneously, resulting in a growing concern that they are at increased risk of iatrogenic harm. This review aims to collate the evidence for the causes of GI symptoms, nutritional issues and associated conditions as well as the burden of polypharmacy in this group of patients. We also describe evidence-based strategies for management, with an emphasis on reducing the risk of iatrogenic harm and improving multidisciplinary team care.